Students Land Surveying, 1994 #1 - Missouri Southern State University (1994)
Students Land Surveying, 1994, 1-3 depict students surveying campus grounds. In image 3, an instructor in Computer Aided Design courses also appears. Therefore, it looks to be as though there's some overlap between these curriculums at the time.